Strategi Endorsement Dalam Membangun Brand Awareness Akun TikTok @Fujiiian - Diana, Adinda; Widhiandono, Doan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to analyze the endorsement strategy used by the TikTok account @fujiiian in building personal brand awareness in the digital era. The research method used is descriptive qualitative with observation and documentation techniques on 16 endorsement videos uploaded during May 2025. The results of the study show that the @fujiiian account, with 36.9 million followers, consistently uploads endorsement content dominated by honest reviews, tutorials, and story telling. The average viewers per endorsement video of 7.42 million and an average engagement rate of 1.03% indicate the effectiveness of the strategy being implemented, where this figure is included in the good category for an account with tens of millions of followers. Active interaction with the audience through comment replies and live streaming also strengthens loyalty and emotional closeness between creators and followers. These findings confirm that an authentic, informative, and interactive endorsement strategy is able to build strong personal brand awareness and strengthen account positioning amidst influencer competition on TikTok. This study provides an academic contribution to the literature on personal branding and endorsement on social media, as well as being a practical reference for content creators who want to build a personal brand effectively on digital platforms.